123k views
3 votes
Dolve the equation
11q-6=3q+8q

User Mayette
by
5.2k points

1 Answer

4 votes

Answer:

no solution

Explanation:

Simplifying

11q + -6 = 3q + 8q

Reorder the terms:

-6 + 11q = 3q + 8q

Combine like terms: 3q + 8q = 11q

-6 + 11q = 11q

Add '-11q' to each side of the equation.

-6 + 11q + -11q = 11q + -11q

Combine like terms: 11q + -11q = 0

-6 + 0 = 11q + -11q

-6 = 11q + -11q

Combine like terms: 11q + -11q = 0

-6 = 0

Solving

-6 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

User NIKHIL C M
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.